2021
DOI: 10.1007/s10067-021-05777-6
|View full text |Cite
|
Sign up to set email alerts
|

Selected clinical parameters and changes in cardiac morphology and function assessed by magnetic resonance imaging in patients with rheumatoid arthritis and ankylosing spondylitis without clinically apparent heart disease

Abstract: Background The aim of the study was to assess the relationship between the occurrence of rheumatoid arthritis (RA) and ankylosing spondylitis (AS) and the cardiac magnetic resonance (CMR) changes in people without clinically overt heart disease. Methods The study group consisted of 74 people (48.81 ± 11.35 years): 29 patients with RA, 23 patients with AS and 22 people from control group. Blood samples were taken to assess laboratory parameters, disease act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Our results suggest that early diagnosis and treatment initiation may prevent not only joint destruction but also myocardial damage. Additionally, we and Greulichet al did not observe differences between the study group and control group in terms of left ventricular size or ejection fraction, as reported also by previous studies [ 8 , 12 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results suggest that early diagnosis and treatment initiation may prevent not only joint destruction but also myocardial damage. Additionally, we and Greulichet al did not observe differences between the study group and control group in terms of left ventricular size or ejection fraction, as reported also by previous studies [ 8 , 12 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…They found that CMR findings indicating myocardial inflammation and fibrosis correlated with RA disease activity. In other studies, which were performed without the use of CMR T1/T2 mapping sequences, focal and diffuse myocardial fibrosis and oedema were frequently seen in RA patients but not in controls [ 7 , 9 , 33 , 37 ]. Abnormal CMR findings were usually associated with higher RA disease activity.…”
Section: Discussionmentioning
confidence: 99%